Fish and fisheries of Bangweulu wetlands, Zambia - Huchzermeyer, Carl Friedrich (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
Bangweulu Wetlands is a 6000 kmÂ² public-private-partnership conservation area in northeastern Zambia, lying on the south-eastern margins of the Bangweulu Swamps, Congo River system. The area is important for wildlife conservation, tourism and as a fishing ground for the local inhabitants. This study provides a baseline of the fish and fisheries of this area. The conservation area is situated on the transition zone between woodland, floodplain and swamp. A total of 42 fish species representing 12 taxonomic families were collected. The fish fauna of the area was characterised by a diversity of small cyprinids (14 species), cichlids (9 species), clariid catfishes (4 species) and mormyrids (4 species). Species such as Clarias gariepinus, C. ngamensis, Marcusenius macrolepidotus, Tilapia rendali, T. sparrmanii and several small Barbus species were shared with adjacent floodplain systems such as the upper Zambezi and Kafue rivers. Fishing was undertaken by fishing groups consisting of a fisherman and his family, or a group of men fishing together. Access to the fishing grounds was controlled by traditional fishing leaders, who collected tribute from fishermen. Fishing groups utilised fixed, distinct fishing areas determined by ancestry. The most important time for fishing was during the drawdown phase of the floodplains, from March until June. During the dry season fewer groups were engaged in fishing, with many having returned to farming activities. The main fishing methods of the floodplain fishery were basket traps and mosquito-mesh funnel nets set into earth fish barriers (fish weirs) constructed on the plains, various mesh sizes of gillnets, hook longlines and seine nets. The use of fish spears, drag baskets and piscicides was of lesser importance. Most fishing gears were constructed of a variety of natural and modern, manufactured materials. The fishery was multi-species and 23 fish species were recorded from in catch. The three most important species in the catches were C. gariepinus, T. rendalli and M. macrolepidotus. Together these contributed 67% by weight to the catch. Catch-per-unit-effort (CPUE) for the different gears was 0.4 Â± 0.3 kg.trap.nightâ »Â¹ for basket traps, 2.7 Â± 4.6 kg.net.nightâ »Â¹ for funnel nets, 0.3 Â± 0.5 kg.50 m net.nightâ »Â¹ for gill nets, 3.5 Â± 6.3 kg.100 hooks.nightâ »Â¹ for longlines, 1.79 Â± 1.11 kg.haulâ »Â¹ for mosquito-mesh seine nets and 6.87 Â± 6.27 kg.haulâ »Â¹ for larger-mesh seine nets. The weight of average daily landings of fishing groups, using a variety of gears was 7.8 Â± 7.4 kg. Fishermen were able to maintain the same catch rate between dry and wet seasons, with no significant differences (p < 0.05) in daily landings between seasons. Yield per fisherman for a seven month season, which required 2-3 relocations due to falling water level, was 1.64 t based on catch assessment, and 1.9 t from a socio-economic survey. A tentative yield per area estimate for the area was 2I7 kg.haâ »Â¹ over the three month shallow-floodplain fishing season. Most fish landed in the fishery were processed into sundried or smoke-dried products. These were used for 1) home consumption, 2) trade with village farmers (from up to 70 km inland of the fishing grounds) in exchange for staple starch meal, and 3) sold to urban fish traders, reaching markets as distant as Lubumbashi in Democratic Republic of Congo. Fish traders toured fishing camps to buy fish, supporting auxiliary industries such as transport and accommodation services. The price for dried fish at source was 3.14 Â± 1.34 USDlkg and the market price reported for the Zambian Copperbelt was 6.14 Â± 2.54 USD/kg. Typical returns on investment in fish trading were estimated as 68-77%. The fishery was considered to be biologically and socially sustainable. By harvesting a seasonally transient assemblage of species with high productivity and biological turnover rates and with life histories adapted to high mortality, fishermen were able to maintain a stable and viable livelihood. Management recommendations for the area were that a fisheries management plan be developed that would seek to strengthen the traditional system of rights-allocation, address problems between fishing and tourism activities, and enhance communication between fisheries and conservation stakeholders. To do this it was recommended that: 1) conservation authorities recognise the importance of the fishery, 2) no changes to current effort levels and fishing methods were necessary, 3) points 1 and 2 above be used to improve communication and trust between conservation authorities and fishermen, 4) customary resource-access mechanisms be understood and strengthened so that local inhabitants' rights to the resource are protected, 5) fishermen help formulate and accept conservation and tourism rules, 6) tourists and guides be made aware of the function of the fishery, 7) a fisheries management forum of key community, government and conservation stakeholders be formed to shape and implement the fisheries management plan, 8) locally-adapted bylaws be created to legitimise crucial floodplain gears currently considered illegal (e.g. mosquito-net gears, fish weirs), 9) no intervention to formalise fish trading be made, and 10) a trained person with a fisheries background be hired oversee the implementation of the recommendations.
Keywords: Bangweulu Swamps (Zambia); Fisheries -- Zambia -- Bangweulu Swamps; Fishes -- Zambia -- Bangweulu Swamps; Fishery management -- Zambia -- Bangweulu Swamps; Fishing -- Zambia -- Bangweulu Swamps; Fishing -- Economic aspects -- Zambia -- Bangweulu Swamps; Fish stock assessment -- Zambia -- Bangweulu Swamps; Fish as food -- Zambia -- Bangweulu Swamps; Conservation of natural resources -- Zambia -- Bangweulu Swamps; Sustainable development -- Zambia -- Bangweulu Swamps